Economic benefits of using a dose dispensing system at hospital units of the Mexican Institute of Social Security. - Rocío Ofelia-Uc Coyoc; Ana Gabriela Pérez-Reynaud; Luis Arturo Coello-Reyes (Instituto Nacional de Salud Pública, 2014)
Objective. To estimate the potential economic benefits at The Mexican Institute of Social Security (IMSS per its abbreviation in spanish) according to the drug expenditure of using drug dispensing system, based on literature information. Materials and methods. A systematic review was performed to identify savings from drugs and reduction of medication errors. The total and mean health expenditure by level of medical attention was calculated using the dispensed collective prescriptions at IMSS during 2009. Three savings scenarios were applied. Results. The total drug savings were in a range of 870.49 Mexican million pesos to 4050.05 Mexican million pesos. Reductions of medication errors can contribute with additional savings up to 3455.56 Mexican million pesos. Conclusion. The drug dispensing system unit generates savings opportunities at the second and third level of attention. The maximum economic benefit was observed in the last level.